2020
DOI: 10.1016/j.neuroscience.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Dysregulation of Dopaminergic System by Maternal Cafeteria Diet During Early Postnatal Development

Abstract: Dopamine is a neurotransmitter crucial for motor, motivational, and reward-related functions. Our aim was to determine the effect of a palatable maternal diet on the transcriptional regulation of dopaminergic-related genes during perinatal development of the offspring. For that, female offspring from dams fed with a control (CON) or a cafeteria (CAF) diet were sacrificed on embryonic day 21 (E21) and postnatal day 10 (PND10). Using micropunch techniques, ventral tegmental area (VTA) and nucleus accumbens(NAc) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…In agreement with these data, we found that programming by CAF diet substantially increases global DNA methylation in the NAc shell of addict offspring that are no longer exposed to CAF diet. Recent evidence have identified that CAF programming promotes D2 dopamine receptor DNA methylation in NAc of the offspring (Rossetti et al, 2020), which potentially might explain the impulsiveness for unhealthy eating. Notably, methyl donors revert the percentage of global DNA methylation and block addiction-like behavior in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these data, we found that programming by CAF diet substantially increases global DNA methylation in the NAc shell of addict offspring that are no longer exposed to CAF diet. Recent evidence have identified that CAF programming promotes D2 dopamine receptor DNA methylation in NAc of the offspring (Rossetti et al, 2020), which potentially might explain the impulsiveness for unhealthy eating. Notably, methyl donors revert the percentage of global DNA methylation and block addiction-like behavior in the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is a neurotransmitter regulating motivational and reward-related functions. A recent preclinical study showed that consumption of cafeteria diets during pregnancy induced epigenetic changes in the dopamine receptor (DAT), dopamine transporter 1 (DRD1) and dopamine transporter 2 (DRD2) genes in the nucleus accumbens (NAc) and VTA, two key regions of the dopaminergic pathway [ 86 ]. In the VTA and NAc, DRD1, DRD2 and DAT expression was decreased at embryonic day 2 and postnatal day 10 in rat female offspring.…”
Section: Underlying Mechanisms By Which Maternal Obesity Programs mentioning
confidence: 99%
“…When these sites are methylated, transcription factors are not able to bind to the promoter regions, and the gene expression decreased. On the contrary, if these sites are demethylated, transcription is activated and gene expression is increased (9,44).…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%
“…The epigenome is influenced by both genetic (e.g. single nucleotide polymorphisms) and environmental factors (8)(9)(10). In this sense, several studies indicate that pesticides can exert toxicity through epigenetic changes [reviewed in (11)].…”
Section: Introductionmentioning
confidence: 99%